Inovasi Pelayanan Publik: Sistem Layanan Adminduk Kolaka Utara Offline, Online dan Terintegrasi (SI LAKU O2T) - Adzam, Muh (Research and Development Agency Ministry of Home Affairs, 2025)
Digital transformation in public services has become an urgent necessity to enhance efficiency, transparency, and inclusivity for citizens. This study aims to analyze the implementation of the Offline, Online, and Integrated Population Administration Service System (SI LAKU O2T) in North Kolaka Regency as a local innovation designed to address infrastructure limitations, digital literacy gaps, and geographical constraints. Using an exploratory qualitative approach through in-depth interviews with 10 key informants, this research examines experiences, perceptions, and challenges encountered in the implementation of SI LAKU O2T. The findings show that the program introduces 12 sub-innovations that combine online services, offline access, and mobile outreach, thereby expanding service coverage, reducing community costs, and increasing public trust in the local government. However, limited internet infrastructure, uneven digital literacy, and varying capacities of village officials remain major obstacles. The local government responds through hybrid service strategies, digital literacy strengthening, and multi-stakeholder collaboration to ensure program sustainability. This study emphasizes that digitalization of public services depends not only on technology, but also on organizational readiness, social capacity, and political commitment. With continuous development, SI LAKU O2T has the potential to become an inclusive, efficient, and adaptive model for digital transformation of public services in other regions of Indonesia. This study recommends strengthening village-level capacity through budget support, digital literacy enhancement, and service standardization as practical contributions to sustaining the innovation.